ASSESSMENT OF THE LIFE CYCLE OF MATERIALS AS A TOOL FOR THE IMPROVEMENT OF LIGHT INDUSTRY PROCESSES AND THE IMPLEMENTATION OF THE PRINCIPLES OF THE CIRCULAR ECONOMY OF MANUFACTURING - IVANISHENA, TETIANA; MANDZYUK, IGOR; TRUKNINA, OKSANA; PEKARSKA, VALERIY (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article analyzes the range of materials that are used for the manufacture of light industry products. In order to improve the environmental characteristics of materials and improve production processes of light industry, a life cycle assessment (LCF) of light industry products made on the basis of primary and secondary raw materials was carried out. Inventory flows during the production of materials were established, the impact of production processes on environmental classes was determined, and the main mechanisms for the management of such processes were proposed.As a result of the analysis of the contributions (LCA) of light industry products based on primary and secondary raw materials, the most influential stages of the processing process were determined. The study included primary data from various processes in the life cycle, including mechanical processing, textile collection, and manual and automated sorting. Based on studies involving mechanical processing and a high percentage of recycled raw materials, the recycled yarn had the potential to reduce impacts including acidification, eutrophication and water consumption. In both cases, the impact of climate change was about a third smaller.According to the analysis, primary fiber content, electricity production, textile collection process, textile waste management and dyeing were found to be the most affected. A small contribution was made by the processing process itself, manual and automatic sorting. In the analysis of textile collection, more efficient route planning can help reduce carbon emissions and reduce costs for companies.
Keywords: life cycle assessment; light industry products; waste processing; waste management